Leadership style types: The Importance of Organizational Culture and Change Management - Bambang Niko Pasla; Martha Sari Ayu; Fathiyah Fathiyah; Bailah Bailah; Fahmi Rasid; Ubaidillah Ubaidillah (Jurnal Prajaiswara, 2022)
Introduction/Main Objectives: This study aims to determine the value of the direct influence between transformational leadership and change management, transformational leadership and organizational culture, organizational culture and change management, and deal with the indirect effect of organizational culture on transformational leadership and change management. Background Problems: In the era of globalization that is increasingly fast and dynamic, an organization must be able to adapt to changes in the environment, where changes in the organization must be managed properly and efficiently. Change management is a systematic and complex process carried out by an organization. One of the steps in determining the direction of change is to select the transformational leadership model, change management, and organizational culture. Research Methods: Review articles on the relationship between transformational leadership, change management, organizational culture, organizational change, and the mediating role of organizational culture on transformational leadership and change management. Finding/Results: There is a positive and significant correlation between transformational leadership and change management, transformational leadership and organizational culture, and organizational culture and change management, where organizational culture has a mediating role in the relationship between transformational leadership and change management. Conclusion: Transformational leadership are very influential on organizational changes and play an essential role in determining the direction of change management and organizational culture, using organizational culture to manage these changes.